INTEGRATING AI AND ENGLISH EDUCATION INTO UZBEKISTAN’S CULTURAL DIPLOMACY FRAMEWORK - Rustamov Alijon Amonkulovich, (TADQIQOTLAR, 2026)
Abstract: This article examines the strategic integration of artificial intelligence and English language pedagogy into the cultural diplomacy framework of the Republic of Uzbekistan. In the era of rapid digital globalization and structural domestic reforms, foreign language  proficiency  serves  as  a critical  conduit  for  soft power  projection, international academic integration, and economic diplomacy. This study evaluates how the  systematic  implementation  of  AI-driven  educational  technologies-such  as intelligent  tutoring  platforms,  automated  neural  translation  models,  and  adaptive linguistic analytics-can optimize Uzbekistan's public diplomacy initiatives. Through a systematic  analysis  of  current  educational  policies  and  digital  infrastructure developments,  the  research  establishes  an  actionable  conceptual  framework  for utilizing automated language training to cultivate a globally competitive workforce while projecting a modern, technologically progressive national narrative. The paper concludes  with  policy  recommendations  designed  to  align  algorithmic  language acquisition with the state's strategic foreign policy objectives.